Flexibility of Women’s Inheritance Distribution in Jambi Malay Society: Compromising Islamic and Customary Law - Al Idrus, Rahmi Hidayati; Ramlah, Ramlah; Yanti, Illy; Mubarrak, Harris; Mukhlisa, Dian (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aimed to determine women's position in the division of inheritance in the Jambi Malay community. This study uses the social legal research method to understand legal phenomena from the social and cultural context in which the law exists. The primary data for this study came from in-depth interviews with religious and traditional leaders, while the secondary data was obtained from relevant literature. The data is then analyzed by editing, organizing, and grouping the research results. The study results indicate legal dualism in inheritance distribution in the Jambi Malay community, namely Islamic and customary law. However, customary law dominates compared to Islamic law. In practice, the flexibility of women's inheritance distribution in the Jambi Malay community aims to find out about the negotiations of the Jambi Malay community in dealing with the equalization of men and women in the distribution of inheritance. Equality is permitted in Islam because, in practice, there must be agreement and approval from each heir